Method for acidification of terephthalylidene dicamphor sulfonate using cation exchange fibers

By converting terephthalene di-camphorsulfonate into terephthalene di-camphorsulfonic acid using cation exchange fibers, the problems of high preparation costs and difficulty in removing salts in the prior art are solved, and an efficient and simple acidification process is achieved.

CN115784942BActive Publication Date: 2025-04-15SERA SOO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210442605.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-13
Filing Date
2022-04-25
Publication Date
2025-04-15
Estimated Expiration
2042-04-25

AI Technical Summary

Technical Problem

The prior art methods for preparing terephthalene dicamphorsulfonic acid have problems with the use of excessive hydrochloric acid, and the need for additional processes to remove the resulting salts.

Method used

The cationic exchange fiber is used to convert terephthalene dicamphorsulfonate into terephthalene dicamphorsulfonic acid through the acidification process, and the acidification effect of high yield and high purity is achieved through reasonable exchange group combination and treatment methods.

Benefits of technology

The preparation process is simplified, the yield, purity and acid conversion rate are improved, and the salts produced during the conversion process are easily removed, reducing the complexity of subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003614615410000041
    Figure BDA0003614615410000041
  • Figure BDA0003614615410000131
    Figure BDA0003614615410000131
  • Figure BDA0003614615410000171
    Figure BDA0003614615410000171
Patent Text Reader

Abstract

The present invention relates to a method for acidifying terephthalene dicamphor sulfonate using cation exchange fiber, and more specifically, to a method for converting terephthalene dicamphor sulfonate into terephthalene dicamphor sulfonic acid using cation exchange fiber. The present invention can provide a method for acidifying terephthalene dicamphor sulfonate with a simple preparation process, high yield, purity and acid conversion rate. The present invention can convert terephthalene dicamphor sulfonate into terephthalene dicamphor sulfonic acid with a high conversion rate using cation exchange fiber, and the salt generated during the conversion is also very easy to remove.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for acidifying terephthalene dicamphor sulfonate using cation exchange fiber, and more particularly, to a method for converting terephthalene dicamphor sulfonate into terephthalene dicamphor sulfonic acid using cation exchange fiber. Background Art

[0002] When the ultraviolet rays contained in sunlight are excessively irradiated on the skin, it will promote the formation of erythema or the production of melanin in skin cells, resulting in spots and blemishes. Ultraviolet rays react with sebum secreted into the epidermis to produce lipid peroxides, which can not only cause skin problems but also cause skin cancer in severe cases.

[0003] Ultraviolet rays are divided into UV-A (320-400nm), UV-B (280-320nm), and UV-C (200-280nm) according to their wavelength. The shorter the wavelength of UV-C, the greater the energy. However, as we all know, most of the short-wavelength ultraviolet rays are absorbed by the atmosphere. Therefore, the ultraviolet rays that directly affect the human body are UV-A and UV-B.

[0004] UV blockers used to prevent skin damage caused by UV rays are roughly divided into chemical UV blockers and physical UV blockers.

[0005] Chemical UV blockers with a chemical UV absorption mechanism include cinnamic acid, salicylic acid, benzophenone, etc. Physical UV blockers with a physical UV scattering and shielding mechanism include inorganic UV blockers such as titanium dioxide and zinc oxide.

[0006] On the other hand, terephthalylidene dicamphor sulfonic acid is an organic UV blocker that blocks UV-A and a portion of UV-B, and is known to have excellent UV blocking effect and antioxidant effect because it is impermeable to water and air.

[0007] Various methods for preparing terephthalylidene dicamphor sulfonic acid are known, and a typical method thereof is a method in which terephthalylidene dicamphor sulfonic acid is produced by acidifying terephthalylidene dicamphor sulfonic acid salt with hydrochloric acid.

[0008] However, since this method uses an excessive amount of hydrochloric acid, the production cost increases, and a separate process for removing the used acid is required.

[0009] Furthermore, there is a problem that an additional step is required to remove salts such as sodium chloride generated in the production process of terephthalylidene dicamphor sulfonic acid.

[0010] Therefore, a method for acidifying terephthalylidene dicamphor sulfonate with simple preparation process, excellent yield and acid conversion rate is needed.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: U.S. Patent No. 4585597 Summary of the invention

[0014] The present invention is used to solve the above-mentioned prior art problems, and its purpose is to provide a method for acidifying terephthalylidene dicamphor sulfonate with simple preparation process, high yield, purity and acid conversion rate.

[0015] In order to achieve the above-mentioned purpose, the present invention provides a method for acidifying terephthalylidene dicamphor sulfonate, which comprises:

[0016] Step (a), preparing an aqueous solution containing terephthalylidene dicamphor sulfonate;

[0017] Step (b), adding the aqueous solution into a column filled with cation exchange fibers for elution;

[0018] step (c), washing the cation exchange fiber by adding purified water to the column; and

[0019] Step (d), mixing the eluted aqueous solution with the washed purified water, filtering to obtain a filtrate, and drying the filtrate to obtain terephthalylidene dicamphor sulfonic acid.

[0020] An embodiment of the present invention is characterized in that the cation exchange fiber comprises at least one exchange group selected from sulfonic acid group, carboxyl group and phosphate group.

[0021] An embodiment of the present invention is characterized in that the cation exchange fiber contains sulfonic acid groups and phosphate groups as exchange groups.

[0022] According to one embodiment of the present invention, a cation exchange fiber containing a sulfonic acid group and a cation exchange fiber containing a phosphate group are used simultaneously as the cation exchange fiber.

[0023] An embodiment of the present invention is characterized in that the weight ratio of the cation exchange fibers containing sulfonic acid groups to the cation exchange fibers containing phosphate groups is 60-90:10-40.

[0024] The invention provides an acidification method for terephthalylidene dicamphor sulfonate with simple preparation process, high yield, high purity and high acid conversion rate.

[0025] The present invention can use cation exchange fiber to convert terephthalylidene dicamphor sulfonate into terephthalylidene dicamphor sulfonic acid at a high conversion rate, and the salt generated during the conversion is also very easy to remove. DETAILED DESCRIPTION

[0026] The following will describe the present invention in detail based on embodiments. The terms, embodiments, etc. used in the present invention are only exemplified to describe the present invention more specifically and help those skilled in the art understand, and the scope of rights of the present invention, etc. should not be interpreted as being limited thereto.

[0027] Unless otherwise defined, technical and scientific terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0028] The present invention relates to an acidification method for terephthalylidene dicamphor sulfonate, which comprises:

[0029] Step (a), preparing an aqueous solution containing terephthalylidene dicamphor sulfonate;

[0030] Step (b), adding the aqueous solution into a column filled with cation exchange fibers for elution;

[0031] step (c), washing the cation exchange fiber by adding purified water to the column; and

[0032] Step (d), mixing the eluted aqueous solution with the washed purified water, filtering to obtain a filtrate, and drying the filtrate to obtain terephthalylidene dicamphor sulfonic acid.

[0033] The step (a) is a step of preparing an aqueous solution containing terephthalylidene dicamphor sulfonate. The aqueous solution can be prepared by mixing 300 to 1500 parts by weight of water, distilled water or purified water with respect to 100 parts by weight of terephthalylidene dicamphor sulfonate and stirring the mixture at 40 to 90°C.

[0034] The terephthalylidene dicamphor sulfonate is represented by the following Chemical Formula 1.

[0035] Chemical formula 1

[0036]

[0037] In the above Chemical Formula 1, M is an alkali metal or N(R1)(R2)(R3)(R4), R1 to R4 are each independently hydrogen or (C1-C7) alkyl, R is (C1-C7) alkyl or (C1-C7) alkoxy, n is 0 or an integer from 1 to 4, and when n is 2 or more, R may be the same or different.

[0038] The step (b) is a step of adding the aqueous solution into a column filled with cation exchange fibers for elution, and the aqueous solution can be added at a rate of 2.5 to 6.5 kg / min.

[0039] Before adding the aqueous solution to the column, the cation exchange fibers filled in the column may be washed with purified water. In this case, 300 to 1000 parts by weight of purified water may be used relative to 100 parts by weight of the cation exchange fibers.

[0040] Fibrous ion exchange fibers are easier to use than particulate ion exchange resins, and their swelling properties in water are significantly better than those of ion exchange resins. Therefore, when filled in a column, they can greatly reduce pressure loss compared to ion exchange resins.

[0041] Furthermore, since ion exchange fibers have more functional groups bonded to the unit chains than ion exchange resins, their ion exchange capacity per unit weight is better than that of ion exchange resins. In ion exchange fibers, graft copolymers have more functional groups than block copolymers and therefore exhibit excellent adsorption capacity.

[0042] As the material of the cation exchange fiber, polyolefins such as polyethylene and polypropylene, polyester, polyamide, polyurethane, polyacrylonitrile, acrylic resin, etc. can be used without limitation.

[0043] The above-mentioned cation exchange fibers include not only short fibers and long fibers, but also aggregates of fibers, namely nonwoven fabrics, mats, nets, fabrics, filter papers, and the like.

[0044] The cation exchange fiber may include at least one exchange group selected from the group consisting of a sulfonic acid group, a carboxyl group, and a phosphoric acid group on the surface.

[0045] The cation exchange fiber into which the sulfonic acid group is introduced can be prepared by the following method.

[0046] The polypropylene fiber is treated with plasma to generate free radicals, and then treated with glycidyl acrylate or glycidyl methacrylate, so that glycidyl acrylate or glycidyl methacrylate can be grafted onto the surface of the polypropylene fiber.

[0047] In this case, preferably, 1 to 10 parts by weight of glycidyl acrylate or glycidyl methacrylate is used relative to 100 parts by weight of the polypropylene fiber.

[0048] Here, sulfonic acid groups can be introduced into the surface of the fiber by treating it with a sulfonating solution, for example, a NaHSO 3 solution.

[0049] Furthermore, after the polypropylene fiber is treated with plasma to generate free radicals in the polypropylene fiber, the fiber may be treated with an oligomer of an acrylate group-containing silane coupling agent and an epoxy group-containing silane coupling agent to graft the oligomer onto the surface of the polypropylene fiber.

[0050] The above oligomer can be prepared by reacting an acrylate group-containing silane coupling agent with an epoxy group-containing silane coupling agent.

[0051] Epoxy-containing silane coupling agents include 2-glycidoxyethylmethyldimethoxysilane, 2-glycidoxyethylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-glycidoxyethyltrimethoxysilane, 2-glycidoxyethyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 3-(3,4-epoxycyclohexyl)propylmethyldimethoxysilane, 3-(3,4-epoxycyclohexyl)propylmethyldiethoxysilane, and the like.

[0052] The silane coupling agents containing acrylate groups include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane and the like.

[0053] Preferably, the weight ratio of the silane coupling agent containing an acrylate group to the silane coupling agent containing an epoxy group is 10-30:70-90. When the weight ratio satisfies the above numerical range, the yield and conversion rate can be maximized.

[0054] In this case, it is preferable to use 1 to 10 parts by weight of the oligomer based on 100 parts by weight of the polypropylene fiber.

[0055] Here, sulfonic acid groups can be introduced on the surface of the fiber by treating it with a sulfonating solution, such as a NaHSO 3 solution.

[0056] The cation exchange fiber into which the above-mentioned phosphate groups are introduced can be prepared by the following method.

[0057] After the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, glycidyl acrylate or glycidyl methacrylate may be treated to graft glycidyl acrylate or glycidyl methacrylate on the surface of the polypropylene fiber.

[0058] In this case, preferably, 1 to 10 parts by weight of glycidyl acrylate or glycidyl methacrylate is used relative to 100 parts by weight of the polypropylene fiber.

[0059] Here, phosphoric acid groups may be introduced into the surface of the fiber by treatment with a phosphoric acid solution.

[0060] Furthermore, after the polypropylene fiber is treated with plasma to generate free radicals in the polypropylene fiber, the oligomer of the silane coupling agent containing an acrylate group and the silane coupling agent containing an epoxy group may be treated to graft the oligomer onto the surface of the polypropylene fiber.

[0061] The above oligomer can be prepared by reacting an acrylate group-containing silane coupling agent with an epoxy group-containing silane coupling agent.

[0062] Preferably, the weight ratio of the silane coupling agent containing an acrylate group to the silane coupling agent containing an epoxy group is 10-30:70-90. When the weight ratio satisfies the above numerical range, the yield and conversion rate can be maximized.

[0063] In this case, it is preferable to use 1 to 10 parts by weight of the oligomer based on 100 parts by weight of the polypropylene fiber.

[0064] Here, phosphoric acid groups may be introduced into the surface of the fiber by treatment with a phosphoric acid solution.

[0065] Also, the cation exchange fiber into which carboxyl groups are introduced can be prepared by the following method.

[0066] After the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, it can be treated with an acrylic acid monomer to graft the acrylic acid monomer on the surface of the polypropylene fiber, thereby introducing a carboxyl group into the surface of the fiber.

[0067] The above-mentioned acrylic monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, methacrylic acid, ethyl acrylic acid, butyl acrylic acid, 2-ethylhexyl acrylate, decyl acrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, decyl methacrylate, etc.

[0068] In this case, preferably, 1 to 10 parts by weight of the acrylic monomer is used relative to 100 parts by weight of the polypropylene fiber.

[0069] Furthermore, after the polypropylene fiber is treated with plasma to generate free radicals in the polypropylene fiber, the copolymer of an acrylate-containing silane coupling agent and an acrylic monomer may be treated to graft the copolymer on the surface of the polypropylene fiber, thereby introducing carboxyl groups into the surface of the fiber.

[0070] The above-mentioned acrylate-containing silane coupling agent includes 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane and the like.

[0071] The above-mentioned acrylic monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, methacrylic acid, ethyl acrylic acid, butyl acrylic acid, 2-ethylhexyl acrylate, decyl acrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, decyl methacrylate, etc.

[0072] Preferably, the weight ratio of the acrylate-containing silane coupling agent to the acrylic monomer is 10-30:70-90. When the weight ratio satisfies the above numerical range, the yield and conversion rate can be maximized.

[0073] In this case, it is preferable to use 1 to 10 parts by weight of the above copolymer with respect to 100 parts by weight of the polypropylene fiber.

[0074] Furthermore, after the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, the copolymer containing an acrylate group, an acrylic acid monomer and 2-hydroxyethyl acrylate (HEA) can be treated to graft the above copolymer on the surface of the polypropylene fiber, thereby introducing carboxyl groups into the surface of the fiber.

[0075] The above-mentioned acrylate-containing silane coupling agent includes 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane and the like.

[0076] The above-mentioned acrylic monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxyethyl methacrylate, carboxypentyl acrylate, carboxypentyl methacrylate, itaconic acid, maleic acid, fumaric acid, methacrylic acid, ethyl acrylic acid, butyl acrylic acid, 2-ethylhexyl acrylate, decyl acrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, decyl methacrylate, etc.

[0077] Preferably, the weight ratio of the acrylate-containing silane coupling agent, acrylic acid monomer and 2-hydroxyethyl acrylate is 2-10:100:20-50. When the weight ratio satisfies the above numerical range, the yield and conversion rate can be maximized.

[0078] In this case, it is preferable to use 1 to 10 parts by weight of the above copolymer with respect to 100 parts by weight of the polypropylene fiber.

[0079] Furthermore, after the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, carboxyl groups can be introduced on the surface of the polypropylene fiber by treating it with an acrylic acid monomer; a copolymer of an acrylate-containing silane coupling agent and an acrylic acid monomer; and a mixture of a copolymer of an acrylate-containing silane coupling agent, an acrylic acid monomer and 2-hydroxyethyl acrylate (HEA).

[0080] Preferably, the weight ratio of the acrylic acid monomer; the copolymer of the silane coupling agent containing an acrylate group and the acrylic acid monomer; and the copolymer of the silane coupling agent containing an acrylate group, the acrylic acid monomer and 2-hydroxyethyl acrylate (HEA) is 100:20-40:5-20. When the weight ratio satisfies the above numerical range, the yield and conversion rate can be maximized.

[0081] In this case, preferably, 1 to 10 parts by weight of the mixture is used relative to 100 parts by weight of the polypropylene fiber.

[0082] The cation exchange fiber of the present invention may contain sulfonic acid groups and phosphoric acid groups as exchange groups.

[0083] To this end, after the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, glycidyl acrylate (or glycidyl methacrylate) may be treated to graft glycidyl acrylate (or glycidyl methacrylate) on the surface of the polypropylene fiber.

[0084] Here, the sulfonic acid group and the phosphoric acid group can be introduced into the surface of the fiber together with the NaHSO 3 solution and the phosphoric acid solution.

[0085] Preferably, the weight ratio of the NaHSO3 to the phosphoric acid is 60-90:10-40. If the weight ratio is less than 60:40, the cation exchange function is reduced, and if it exceeds 90:10, the durability and processability of the fiber are reduced.

[0086] Furthermore, the cation exchange fibers may be composed of both sulfonic acid group-containing cation exchange fibers and phosphate group-containing cation exchange fibers.

[0087] Preferably, the weight ratio of the cation exchange fibers containing sulfonic acid groups to the cation exchange fibers containing phosphate groups is 60-90:10-40. If the weight ratio is less than 60:40, the cation exchange function is reduced, and if it exceeds 90:10, the durability and processability of the fiber are reduced.

[0088] The cation exchange fiber of the present invention may contain sulfonic acid groups, phosphoric acid groups and carboxyl groups as exchange groups.

[0089] To this end, after the polypropylene fiber is treated with plasma to form free radicals in the polypropylene fiber, glycidyl acrylate (or glycidyl methacrylate) and acrylic acid monomers may be treated to graft glycidyl acrylate and acrylic acid monomers on the surface of the polypropylene fiber.

[0090] Here, sulfonic acid groups, phosphoric acid groups and carboxyl groups can be introduced into the surface of the fiber together with treatment with NaHSO3 solution and phosphoric acid solution.

[0091] Preferably, the weight ratio of the glycidyl acrylate to the acrylic acid monomer is 60-90:10-40. If the weight ratio is less than 60:40, the cation exchange function is reduced, and if it exceeds 90:10, the durability and processability of the fiber are reduced.

[0092] Furthermore, preferably, the weight ratio of the NaHSO 3 to the phosphoric acid is 60-90:10-40. If the weight ratio is less than 60:40, the cation exchange function is reduced, and if it exceeds 90:10, the durability and processability of the fiber are reduced.

[0093] In this case, instead of the acrylic monomer, a copolymer of an acrylate-containing silane coupling agent and an acrylic monomer; a copolymer of an acrylate-containing silane coupling agent, an acrylic monomer, and 2-hydroxyethyl acrylate (HEA); or a mixture of a copolymer of an acrylic monomer, an acrylate-containing silane coupling agent, and an acrylic monomer, and a copolymer of an acrylate-containing silane coupling agent, an acrylic monomer, and 2-hydroxyethyl acrylate (HEA) can be used.

[0094] Furthermore, the cation exchange fibers may include sulfonic acid group-containing cation exchange fibers, phosphate group-containing cation exchange fibers, and carboxyl group-containing cation exchange fibers.

[0095] Preferably, the weight ratio of the cation exchange fibers containing sulfonic acid groups, the cation exchange fibers containing phosphate groups and the cation exchange fibers containing carboxyl groups is 100:20-50:5-20. When the weight ratio satisfies the above numerical range, the cation exchange function of the fibers can maximize durability and processability.

[0096] The above step (c) is a step of washing the cation exchange fiber by adding purified water to the above column.

[0097] After the aqueous solution is added, water, distilled water or purified water may be added to the column to elute the aqueous solution or terephthalylidene dicamphor sulfonic acid remaining in the column and the cation exchange fiber.

[0098] In this case, 300 to 1200 parts by weight of purified water may be used relative to 100 parts by weight of the cation exchange fiber.

[0099] The step (d) is a step of mixing the eluted aqueous solution with the purified water for washing, filtering to obtain a filtrate, and drying the filtrate to obtain terephthalylidene dicamphor sulfonic acid. The obtained filtrate is distilled under reduced pressure, concentrated and dried to obtain solid terephthalylidene dicamphor sulfonic acid.

[0100] The terephthalylidene dicamphor sulfonic acid is represented by the following Chemical Formula 2.

[0101] Chemical formula 2

[0102]

[0103] In the above Chemical Formula 2, R is a (C1-C7) alkyl group or a (C1-C7) alkoxy group, n is 0 or an integer from 1 to 4, and when n is 2 or more, R may be the same or different.

[0104] Hereinafter, the present invention will be described in detail by way of examples and comparative examples. The following examples are merely illustrative for the purpose of implementing the present invention, and the content of the present invention is not limited by the following examples.

[0105] (Example 1)

[0106] After 100 parts by weight of the polypropylene fiber was treated with argon plasma to form free radicals in the polypropylene fiber, 5 parts by weight of glycidyl methacrylate was treated to graft glycidyl methacrylate on the surface of the polypropylene fiber.

[0107] Here, sulfonic acid groups were introduced into the surface of the fiber by treatment with a NaHSO3 solution.

[0108] 4 kg of disodium terephthalylidene dicamphorsulfonate and 24 kg of purified water were stirred at 60° C. to prepare an aqueous solution.

[0109] Into a column filled with 5 kg of the polypropylene fibers into which the sulfonic acid groups were introduced, 20 kg of purified water was added to wash the fibers.

[0110] After the washing was completed, the aqueous solution was added to the column at a rate of 6 kg / min and eluted.

[0111] After the addition of the aqueous solution, 20 kg of purified water was added to the column to wash the fibers.

[0112] The eluted aqueous solution and the purified water for washing were mixed and filtered to obtain a filtrate, and the filtrate was distilled under reduced pressure to obtain solid terephthalylidene dicamphor sulfonic acid (yield 96.5%).

[0113] The obtained solid was analyzed by inductively coupled plasma emission mass spectrometry (ICP-Mass) and the Na content was measured, whereby the conversion rate of the converted terephthalylidene dicamphor sulfonic acid was 98.6%.

[0114] 1 H-NMR(D2O)δ(ppm):0.85(s,6H),1.19(s,6H),1.61(m,2H),1.72(m,2H),2.32(m, 2H),2.74(m,2H),2.99(d,2H),3.18(m,2H),3.49(d,2H),7.22(s,2H),7.59(s,4H)

[0115] (Example 2)

[0116] After 100 parts by weight of the polypropylene fiber was treated with argon plasma to form free radicals in the polypropylene fiber, 5 parts by weight of glycidyl methacrylate was treated to graft glycidyl methacrylate on the surface of the polypropylene fiber.

[0117] Here, sulfonic acid groups were introduced into the surface of the fiber by treatment with a NaHSO3 solution.

[0118] 4 kg of disodium terephthalylidene dicamphorsulfonate and 24 kg of purified water were stirred at 60° C. to prepare an aqueous solution.

[0119] Into a column filled with 5 kg of the polypropylene fibers into which the sulfonic acid groups were introduced, 20 kg of purified water was added to wash the fibers.

[0120] After the washing was completed, the aqueous solution was added to the column at a rate of 3 kg / min and eluted.

[0121] After the addition of the aqueous solution, 20 kg of purified water was added to the column to wash the fibers.

[0122] The eluted aqueous solution and the purified water for washing were mixed and filtered to obtain a filtrate, and the filtrate was distilled under reduced pressure to obtain solid terephthalylidene dicamphor sulfonic acid.

[0123] (Example 3)

[0124] After 100 parts by weight of the polypropylene fiber was treated with argon plasma to form free radicals in the polypropylene fiber, 5 parts by weight of glycidyl methacrylate was treated to graft glycidyl methacrylate on the surface of the polypropylene fiber.

[0125] Here, the sulfonic acid group and the phosphoric acid group are introduced into the surface of the fiber by treatment with a NaHSO3 solution and a phosphoric acid solution. In this case, the weight ratio of NaHSO3 to phosphoric acid is 80:20.

[0126] 4 kg of disodium terephthalylidene dicamphorsulfonate and 24 kg of purified water were stirred at 60° C. to prepare an aqueous solution.

[0127] 20 kg of purified water was added to a column filled with 5 kg of polypropylene fibers into which the sulfonic acid groups and phosphoric acid groups were introduced, to wash the fibers.

[0128] After the washing was completed, the aqueous solution was added to the column at a rate of 6 kg / min and eluted.

[0129] After the addition of the aqueous solution, 20 kg of purified water was added to the column to wash the fibers.

[0130] The eluted aqueous solution and the purified water for washing were mixed and filtered to obtain a filtrate, and the filtrate was distilled under reduced pressure to obtain solid terephthalylidene dicamphor sulfonic acid.

[0131] (Example 4)

[0132] The copolymer was prepared by reacting 5 parts by weight of 3-methacryloxypropyltrimethoxysilane, 100 parts by weight of methacrylic acid, and 30 parts by weight of 2-hydroxyethyl acrylate (HEA).

[0133] After 100 parts by weight of polypropylene fiber was treated with argon plasma to form free radicals in the polypropylene fiber, 4 parts by weight of glycidyl methacrylate and 1 part by weight of the copolymer were treated to graft glycidyl methacrylate and the copolymer on the surface of the polypropylene fiber.

[0134] Here, the sulfonic acid group, phosphoric acid group and carboxyl group are introduced into the surface of the fiber by treatment with a NaHSO3 solution and a phosphoric acid solution. In this case, the weight ratio of NaHSO3 to phosphoric acid is 80:20.

[0135] 4 kg of disodium terephthalylidene dicamphorsulfonate and 24 kg of purified water were stirred at 60° C. to prepare an aqueous solution.

[0136] 20 kg of purified water was added to a column filled with 5 kg of polypropylene fibers into which the sulfonic acid group, phosphoric acid group, and carboxyl group were introduced, to wash the fibers.

[0137] After the washing was completed, the aqueous solution was added to the column at a rate of 6 kg / min and eluted.

[0138] After the addition of the aqueous solution, 20 kg of purified water was added to the column to wash the fibers.

[0139] The eluted aqueous solution and the purified water for washing were mixed and filtered to obtain a filtrate, and the filtrate was distilled under reduced pressure to obtain solid terephthalylidene dicamphor sulfonic acid.

[0140] (Comparative Example 1)

[0141] Dissolve 10 g of disodium terephthalylidene camphor sulfonate in 30 ml of water and 30 ml of concentrated hydrochloric acid. After refluxing for 1 hour, concentrate and cool, and filter the resulting solid. Wash with 6N hydrochloric acid, dry under reduced pressure at 80°C, and dry under reduced pressure at 100°C to obtain terephthalylidene camphor sulfonic acid.

[0142] (Comparative Example 2)

[0143] An aqueous solution was prepared by dissolving 10 g of disodium terephthalylidene dicamphorsulfonate in 100 ml of water.

[0144] 100 g of a cation exchange resin (styrene-divinylbenzene copolymer) into which a sulfonic acid group was introduced was added to the aqueous solution, and the mixture was stirred at room temperature for 5 hours to prepare a mixed solution.

[0145] The mixed solution was filtered to remove the resin, and the obtained filtrate was washed with 50 ml of water and then distilled under reduced pressure to obtain solid terephthalylidene dicamphor sulfonic acid.

[0146] The yield and conversion rate of the terephthalylidene dicamphor sulfonic acid prepared in the above examples and comparative examples were measured, and the results are shown in Table 1 below.

[0147] Table 1

[0148]

[0149] From the results in Table 1 above, it can be seen that Examples 1 to 4 have excellent yields and conversion rates, and in particular, Example 4 has the most excellent properties.

[0150] On the contrary, it is found that the above characteristics of Comparative Examples 1 and 2 are inferior to those of the Example.

Claims

1. A method for acidifying terephthalylidene camphor sulfonate, comprising: Step (a), preparing an aqueous solution containing terephthalylidene dicamphor sulfonate; Step (b), adding the aqueous solution into a column filled with cation exchange fibers for elution; Step (c), washing the cation exchange fiber by adding purified water to the column; as well as Step (d), mixing the eluted aqueous solution with the washed purified water and filtering to obtain a filtrate, and drying the filtrate to obtain terephthalylidene dicamphor sulfonic acid, It is characterized in that The cation exchange fiber contains sulfonic acid groups and phosphate groups as exchange groups. The above cation exchange fiber is prepared by the following steps: After the fiber is treated with plasma to form free radicals in the fiber, the fiber is treated with an oligomer of a silane coupling agent containing an acrylate group and a silane coupling agent containing an epoxy group to graft the oligomer on the surface of the fiber; The grafted fibers were treated with NaHSO3 solution and phosphoric acid solution to introduce sulfonic acid and phosphoric acid groups into the fiber surface. The oligomer is prepared by reacting an acrylate-containing silane coupling agent and an epoxy-containing silane coupling agent. The weight ratio of the silane coupling agent containing an acrylate group to the silane coupling agent containing an epoxy group is 10-30:70-90. The weight ratio of the above-mentioned NaHSO3 to phosphoric acid is 60-90:10-40.

Citation Information

Patent Citations

  • 3-benzylidene-camphors, process for their preparation and their use in protection against UV rays

    US4585597A

  • Multifunctional polymer fiber

    WO2019160231A1

  • Method for acidifying terephthalylidene dicamphor sulfonate

    WO2021153847A1